Evidence for purine nucleoside phosphorylase (PNP) release from rat C6 glioma cells. Issue 2 (April 2017) - Giuliani, Patricia; Zuccarini, Mariachiara; Buccella, Silvana; Peña‐Altamira, Luis Emiliano; Polazzi, Elisabetta; Virgili, Marco; Monti, Barbara; Poli, Alessandro; Rathbone, Michel P.; Iorio, Patrizia Di; Ciccarelli, Renata; Caciagli, Francesco
Abstract : Purine nucleoside phosphorylase (PNP) is a cytosolic enzyme that metabolizes inosine (INO) and guanosine (GUO) into hypoxanthine (HYPO) and guanine (GUA), respectively. It is released from glial cells in the pericellular fluid, where it is metabolically active. Together with other enzymes it contributes to controlling extracellular purine levels and to protecting brain cells, mainly neurons that are less furnished with PNP, from abnormal interactions with these substances. Abstract: Intracellular purine turnover is mainly oriented to preserving the level of triphosphate nucleotides, fundamental molecules in vital cell functions that, when released outside cells, act as receptor signals. Conversely, high levels of purine bases and uric acid are found in the extracellular milieu, even in resting conditions. These compounds could derive from nucleosides/bases that, having escaped to cell reuptake, are metabolized by extracellular enzymes similar to the cytosolic ones. Focusing on purine nucleoside phosphorylase (PNP) that catalyzes the reversible phosphorolysis of purine (deoxy)‐nucleosides/bases, we found that it is constitutively released from cultured rat C6 glioma cells into the medium, and has a molecular weight and enzyme activity similar to the cytosolic enzyme. Cell exposure to 10 μM ATP or guanosine triphosphate (GTP) increased the extracellular amount of all corresponding purines without modifying the levels/activity of released PNP, whereas selective activation of ATP P2Y1 or adenosine A2A metabotropic receptors increased PNP release and purine base formation. The reduction to 1% in oxygen supply (2 h) to cells decreased the levels of released PNP, leading to an increased presence of extracellular nucleosides and to a reduced formation of xanthine and uric acid. Conversely, 2 h cell re‐oxygenation enhanced the extracellular amounts of both PNP and purine bases. Thus, hypoxia and re‐oxygenation modulated in opposite manner the PNP release/activity and, thereby, the extracellular formation of purine metabolism end‐products. In conclusion, extracellular PNP and likely other enzymes deputed to purine base metabolism are released from cells, contributing to the purinergic system homeostasis and exhibiting an important pathophysiological role.